Robot Seed Planter Based on Distance - Razak, Syazwan; Mat Akir, Rohaida (Evolution in Electrical and Electronic Engineering, 2021)
The precision and time play an important role on the outcome of the yield. This paper is about to introduce the autonomous vehicle system in the agriculture system. This will help in increasing productivity and also reduce time consumed to plant seeds in agriculture. Planting seeds on larger scale using manual method will consume time, less precision and also labor-intensive. Thus, the objective of this project is to design an autonomous robot and also a system that approximately move the vehicle to a place that had been set. In this project, the microcontroller that is used are the ArduPilot, GPS module, Telemetry kit and also a mission planner application. The scope of the project is the positioning and also localization of seeds planted between each other. The system had been tested and was conducted to find its accuracy by acquiring the distance of the car moved using the system designed and differentiate it with the set distance. The design of the autonomous robot was successful and the test for the system had shown the accuracy of the system and also the average accuracy of the system are very low that has an error of 1.11%. In conclusion, the design of the robot and the system is successful. But for the in the real-world situation, it is not ready due to the large error. For future work we, need to use a different type of microcontroller that is more advance. Other than that, we need to change the GPS module that is more precise so it can detect the distance more precise. Other than that, we need to use a higher frequency telemetry kit to have a better connection from the device to the application controller.